(untitled) (Bangladesh Journal of Microbiology, 2020)
Blood and its components are essential for life and often required to be transfused in critical health condition. However, such transfusion is reported to be associated with the risk of transfusion transmissible infections (TTIs) with notable pathogens e.g. Hepatitis B virus (HBV), Hepatitis C virus (HCV), Human immunodeficiency virus (HIV) and Treponema pallidum. These pathogens are of major public health concern especially in developing countries like Bangladesh. Increase in the number of TTIs is found to be associated with improper management of safe blood transfusion protocol (SBTP) and unethical practices. This study focuses on the prevalence of such TTIs in volunteers’ blood collected between October and December 2018 from Sakhawath Memorial and Avicina Hospitals in Shirajgong district. Prevalence rate of HIV, HBsAg, HCV and Treponema pallidum were 1.2%, 6.8%, 0.8% and 1.6%, respectively. Among the infected individuals, 75% HIV positive cases were professionals, 70% HCV infected cases wwere from other professional groups and 50% of syphilis infected were homemakers. Male donors showed higher incidence rate of HBV (65%), HCV (72%) and HIV (85%) compared to the female donors. Although the findings of the study showed prevalence of TTIs in volunteer blood donors (VBDs) at an alarming rate, most of the infected individuals were not aware of their infections and potential risk of transmission from them. It is necessary to create awareness among blood donors about possible causes of transmission and prevention of infection . Such initiative from both governmental and non-governmental organizations can help reduce TTIs among VBDs. Bangladesh J Microbiol, Volume 36 Number 2 December 2019, pp 105-109